30.4k views
2 votes
Pleasee help me

2t+ 1 = 3t-1 + 3
3 4



User MiguelSlv
by
5.4k points

2 Answers

1 vote

Answer:

t = - 2

Explanation:


(2t + 1)/(3) = ((3t-1) + 3)/(4)

First we need to cross multiply to get rid of the division to make it easier to solve.

Multiply 2t+1 by 4 and (3t-1) + 3 by 3

4 ( 2t + 1 ) = 3 ( ( 3t - 1 ) + 3 ) On the right we need to combine terms.

4 ( 2t + 1 ) = 3 ( 3t - 1 + 3 )

4 ( 2t + 1 ) = 3 ( 3t + 2 ) Multiply

4 * 2t + 4 * 1 = 3 * 3t + 3 * 2 Remember order of operations. Multiplication comes before addition and subtraction.

4 * 2t + 4 * 1 = 3 * 3t + 3 * 2

8t + 4 = 9t + 6 Subtract 8t from each side

8t - 8t + 4 = 9t - 8t + 6

4 = t + 6 Subtract 6 from each side

4 - 6 = t + 6 - 6

4 - 6 = t

- 2 = t

User Jus
by
5.5k points
2 votes

Answer:

t = -1

Explanation:


2t + 1 = 3t - 1 + 3

Collect like terms and simplify


2t - 3t = - 1 + 3 - 1 \\ - t = 1

Divide through by -1


( - t)/( - 1) = ( 1)/( - 1) \\ t = - 1

User Carson Crane
by
5.1k points